2006
DOI: 10.1302/0301-620x.88b6.17459
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous drilling for the treatment of secondary osteonecrosis of the knee

Abstract: Osteonecrosis of the knee comprises two separate disorders, primary spontaneous osteonecrosis which is often a self-limiting condition and secondary osteonecrosis which is associated with risk factors and a poor prognosis. In a series of 61 knees (38 patients) we analysed secondary osteonecrosis of the knee treated by a new technique using multiple small percutaneous 3 mm drillings. Total knee replacement was avoided in 59 knees (97%) at a mean follow-up of 3 years (2 to 4). Of the 61 knees, 56 (92%) had a suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 65 publications
0
29
0
3
Order By: Relevance
“…There is little consensus regarding treatment options for osteonecrosis and many different therapeutic approaches have been proposed. These options range from activity modification to surgical intervention including arthroscopic debridement [10], core decompression [11], osteotomy [9], osteochondral grafting [2], and partial or total knee arthroplasty [14,15]. Nonoperative treatment is largely ineffective in patients with symptomatic osteonecrotic lesions of the knee, leading to high rates of failure [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little consensus regarding treatment options for osteonecrosis and many different therapeutic approaches have been proposed. These options range from activity modification to surgical intervention including arthroscopic debridement [10], core decompression [11], osteotomy [9], osteochondral grafting [2], and partial or total knee arthroplasty [14,15]. Nonoperative treatment is largely ineffective in patients with symptomatic osteonecrotic lesions of the knee, leading to high rates of failure [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nonoperative treatment is largely ineffective in patients with symptomatic osteonecrotic lesions of the knee, leading to high rates of failure [12]. Retrograde drilling with small- [11] or large-diameter trephines, with or without bone grafting, arthroscopic debridement [10], and osteotomy [9] have been postulated for early stages (modified Ficat/Arlet Stages I-II) of osteonecrosis, with reported clinical success rates between 72% in medium-sized lesions and 92% in small lesions at short-term followup. None of these modalities has proven reproducibly effective in treating symptomatic, high-grade (modified Ficat/Arlet Stages III-IV) osteonecrotic lesions of the distal femur, often necessitating total joint arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…At the latest follow-up, however, these three knees were still categorized as having poor outcomes (Knee Society scores <80 points). Marulanda et al 34 reported low rates of complications and morbidity with core decompression.…”
Section: Core Decompressionmentioning
confidence: 99%
“…Before that time, that method had been used successfully in the treatment of osteonecrosis of the hip. 33 In 2006, Marulanda et al 34 used core decompression and modified the procedure with the percutaneous drilling of several 3-mm holes in each of 61 knees (38 patients; average follow-up, 3 years; range, 2-4 years). They reported a 92% (56 knees) successful clinical outcome, which they defined as a postoperative Knee Society score of 80 or more points.…”
Section: Core Decompressionmentioning
confidence: 99%
“…Arthroscopic debridement, tibial osteotomy, osteochondral grafting, resurfacing techniques, and partial or total knee replacement are options for surgical treatment [11][12][13][14] . All have been reported to be efficacious in the treatment of knee osteochondral defects.…”
Section: Case Reportmentioning
confidence: 99%